Structure-dependent vibrational dynamics of Mg(BH4)2 polymorphs probed with neutron vibrational spectroscopy and first-principles calculations. Issue 36 (2nd September 2016) - Dimitrievska, Mirjana; White, James L.; Zhou, Wei; Stavila, Vitalie; Klebanoff, Leonard E.; Udovic, Terrence J.
Abstract : Neutron vibrational spectroscopy and DFT calculations are used in order to gain deeper insights into the structure-dependent vibrational properties of Mg(BH4 )2 polymorphs. Abstract : The structure-dependent vibrational properties of different Mg(BH4 )2 polymorphs (α, β, γ, and δ phases) were investigated with a combination of neutron vibrational spectroscopy (NVS) measurements and density functional theory (DFT) calculations, with emphasis placed on the effects of the local structure and orientation of the BH4 − anions. DFT simulations closely match the neutron vibrational spectra. The main bands in the low-energy region (20–80 meV) are associated with the BH4 − librational modes. The features in the intermediate energy region (80–120 meV) are attributed to overtones and combination bands arising from the lower-energy modes. The features in the high-energy region (120–200 meV) correspond to the BH4 − symmetric and asymmetric bending vibrations, of which four peaks located at 140, 142, 160, and 172 meV are especially intense. There are noticeable intensity distribution variations in the vibrational bands for different polymorphs. This is explained by the differences in the spatial distribution of BH4 − anions within various structures. An example of the possible identification of products after the hydrogenation of MgB2, using NVS measurements, is presented. These results provide fundamental insights of benefit to researchers currently studying these promising hydrogen-storage materials.